Seguimiento de los egresados de la facultad de odontología de la Universidad de Antioquia desde 1941 hasta 2011. Parte I: caracterización sociodemográfica (2014)
ABSTRACT: Constant follow-up to graduates is one of the university’s duties because graduates are the visible body of the process the institution provides society with. Information for this study was gathered by monitoring graduates from Universidad de Antioquia School of Dentistry from 1941 to 2011. The results were sorted out in three groups (socio-demographic characteristics, employment characteristics, and school-graduate relationship and social impact). This first publication pretends to inform on the number of graduates and their socio-demographic characteristics. Methods: this was a descriptive, retrospective, cross-sectional study with a structured, triangulated, validated survey and a pilot test, complying with ethical principles and ensuring confidentiality in the information. Results: in the period of study there were 3.553 graduates. The sample included 791 graduates, and as 209 were dead, finally 582 responded the survey. The number of graduates has increased for decades, in a ratio of 10 men for every woman in the past to 2 women for every man nowadays. The average age of graduates is 39.5 years. Most were born in Antioquia (Colombia), where they still reside and work; 90.9% did a rural internship. 42.1% pursued further non-formal and formal studies, like this: 35.9% specialization, 4.5% master’s studies, 1.4% doctorate, and 0.3% postdoctoral. 96.4% work in dental practice. Conclusions: graduates from Universidad de Antioquia School of Dentistry’s undergraduate program have increased in number for decades and there is a higher proportion of women. Most were born in Antioquia, were they still work and reside; they are interested in continuing education and they work as dentists, in consonance with the professional role for which they were trained.